Potential Collapse Based on Discontinuity Plane In The Andesite Quary Of Mount Geulis, Jatinangor District, Sumedang Regency, West Java - Taufiq, Mochamad Muslim; Sophian, Raden Irvan; Khoirullah, Nur; Zakaria, Zulfialdi (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
Landslide are natural disasters that often occur in West Java, in 2020 landslides have occurred 852 times. In an effort to prevent the occurrence of rock landslides, it is necessary to study the stability of rock slopes, so it is necessary to evaluate the discontinuity of the rock and take engineering geological. The purpose of this study is to analyze the stability of rock slopes in the study area so that the types of landslides that can occur can be known. Method used is Kinematic Analysis where the object of research is an andesite outcrop located at the northwest foot of Mount Geulis, Cinanjung Village, Jatinangor District. Kinematic analysis is an analysis of the movement of objects without considering the forces that cause them. Various types of slope failure are associated with geological structures that result in a discontinuity plane in the rock body. The results of the study are in the form of determining the potential for landslides that can occur in the research area. Based on the kinematic analysis of the types of failure in the research area that can occur are wedge types in the MT-2, MT-5, and MT-6 segments and toppling types in the MT-3, MT-4, MT-7 segments and Planar failure found in the MT - 1 segment. potential failure in the study area are toppling and wedge with percentage values for the possibility of landslides were obtained, namely: wedge failure is 1.82% - 3.91% and toppling failure is 21.82% - 38.95% and Planar failure is 55.81%